Seasonal training and match load and micro-cycle periodization in male Premier League academy soccer players - Hannon, M. P.; Coleman, N. M.; Parker, L. J. F.; McKeown, J.; Unnithan, V. B.; Close, G. L.; Drust, B.; Morton, J. P. (Journal of Sports Sciences, 2021)
We quantified on pitch external loading of English Premier League (EPL) academy soccer players (n=76; U12-U18 age groups) over an entire competitive season. Mean accumulative weekly duration and total distance, respectively, was similar in the U12 (329±29 min; 19.9±2.2 km), U13 (323±29 min; 20.0±2.0 km) and U14 (339±25 min; 21.7±2.0 km; P>0.05 for all comparisons) age-groups, though all teams were less than U15 (421±15 min; 26.2±2.1 km), U16 (427±20 min; 25.9±2.5 km) and U18 (398±30 min; 26.1±2.6 km) players (P<0.05 for all comparisons). Mean weekly high-speed running and sprint distance was not different between U12 (220±95 m and 6±9 m respectively), U13 (331±212 m and 6±27 m) and U14 (448±193 m and 21±29 m) age-groups (P>0.05 for all pairwise comparisons) though all squads were less than U15 (657±242 m and 49±98 m), U16 (749±152 m and 95±55 m) and U18 (979±254 m and 123±56 m) age-groups (P<0.05 for all pairwise comparisons). Data demonstrate that absolute weekly training volume in EPL academy soccer players increases throughout the academy pathway. Furthermore, although U16-U18 players are capable of achieving similar training and match volumes as previously reported in adult EPL players, they do not yet achieve the absolute intensities of adult EPL players.